Modeling the Interactions between Poly(N-Vinylpyrrolidone) and Gas Hydrates: Factors Involved in Suppressing and Accelerating Hydrate Growth - Wathen, Brent; Kwan, Peter; Jia, Zongchao; Walker, Virginia K. (High Performance Computing Systems and Applications, 2010)
Gas hydrates represent both a bane and a potential boon to the oil and gas industry, and considerable research into hydrate formation has been undertaken. We have recently developed a multi-threaded version of a Monte Carlo crystal growth algorithm and applied it to simulate the growth of large structure II gas hydrates. This algorithm allows for the introduction of non-crystal molecules during simulations to study their effects on crystal growth rates and morphologies. Here, we report on our initial simulations of hydrate growth in the presence of poly(N-vinylpyrrolidone) (PVP). We have surveyed the PVP-hydrate interaction space by performing numerous simulations, each with a unique PVP-hydrate docking orientation. This survey produced a broad range of hydrate growth rates, ranging from almost complete suppression through to significant growth enhancement. The effect that PVP has on gas incorporation at crystal surfaces appears to be critical for differentiating between crystal growth inhibition and enhancement.